If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 9x = 11x Solving 18 + 9x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 18 + 9x + -11x = 11x + -11x Combine like terms: 9x + -11x = -2x 18 + -2x = 11x + -11x Combine like terms: 11x + -11x = 0 18 + -2x = 0 Add '-18' to each side of the equation. 18 + -18 + -2x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = 0 + -18 -2x = 0 + -18 Combine like terms: 0 + -18 = -18 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| -4n-17=2(-3-2) | | x-5=73 | | 3(x-8)=-6(1-x) | | 7(4+2x)-(1+7x)=7x-7+4-6x | | 5(x+4)=2x-7 | | 4x-2y=y+8 | | 4x+-12=6+8 | | -2(4p+4)=-8p+63 | | -4(2x-6)+8x=5x+24+4 | | 2t+5-7=4 | | 6x+3(-2x+2)=6 | | -11+14t+13p-4t-3p+21= | | 8x^2+2x+15=0 | | x(5x+2)=24 | | 8(v+1)-8(8+5v)=40 | | (w+2)=2w^2+9w+10 | | 4/9(2x-4)=48 | | a=1/2(b+b) | | 4h+2h=.72 | | -2x^3-8x^2+10x=0 | | (-x^2)+6x-5=12 | | -52=-2(a+1)+2(7a+5) | | -126=7(-3x+2)+x | | 3x-(2x+3)=-18 | | -126=7(-3+2)+x | | 4x+10=6x-38 | | -7(1-2n)=105 | | 2/3x+0.5x=x+2 | | 5+2(5x-22)= | | (1-x)((2-x)(1-x)-1)-(-1)((x-1)-0)=0 | | -264=8(6x-3) | | 125=6n+5(4n-1) |